Breakfast skipping behaviour among secondary school students in Bachok, Kelantan - Ismail, Nur Ain Ashikin; Mohd Nawi, Norhidayah; Abdul Karim, Noraida; Mahamed Ali, Faliza; Mohd Isa, Sulaiha (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Breakfast is often labeled as the day’s most vital meal, yet many young people continue to omit it despite its nutritional and health value. In Malaysia, most investigations have concentrated on urban adolescents, while breakfast habits in rural communities remain less understood. This research aimed to determine how often secondary school students in Bachok, Kelantan skip breakfast and to identify links with perceived weight status, socio-demographic variables, and personal routines. Using the Health Promotion Model and the Theory of Planned Behavior as guiding frameworks, a cross-sectional survey was carried out among 259 students chosen through simple random sampling. Data were collected with a validated questionnaire and analyzed using chi-square tests. Results indicated that although the majority recognized the importance of breakfast, a sizeable group admitted to skipping it. Key reasons included beliefs about body weight, lack of prepared meals, low appetite, and food dislike. In contrast to earlier urban-based findings, the shortage of time was not a major reason in this rural context. Instead, household environment, food access, and body image concerns were the strongest influences. These findings highlight the need for tailored strategies to improve adolescent eating practices, including correcting misconceptions about weight control, strengthening family and school support, and ensuring rural canteens provide nutritious, appealing breakfast choices.